Analisis Efektivitas Tata Letak pada Excelso di Gress Mall Gresik - Rivaldy Raihan Syams; Ayu Balqis Salsabilah; Moh. Agung Surianto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This study aims to analyze the effectiveness of the layout at the Excelso outlet in Gress Mall, Gresik Regency. Through the Activity Relationship Chart (ARC) approach, this research evaluates the relationship between facilities and infrastructure, focusing on blank-spot areas identified from the pre-survey results. Literature studies on layout, its purpose, benefits, types of layout, and factors that make an effective layout are the basis for analyzing the research results. The research method includes research design with ARC analysis, primary and secondary data collection through interviews, observation, and documentation. The results show that there is a blank-spot in the outdoor area that can be overcome by strategically placing waiters. The ARC diagram illustrates the relationship of activities and interrelationships between products at Excelso Gress Mall. Understanding the effective layout is expected to provide recommendations for improvement to increase customer satisfaction and operational efficiency.